The effect of ethanol extract of kirinyuh leaf (Chromolaena odorata L) on the allergy healing of rabbit (lepus curpaneums) - Teuku Husni TR; Ikbal ISMAİL; Keıshya MAURİEZA (Journal of Syiah Kuala Dentistry Society, 2022)
Allergic rhinitis is one of the world's most common diseases and remains alive. The following diseasesare often found in otorhinolaryngology and constitute a significant health problem worldwide. Symptoms of nasalhyperactivity and hyperresponsiveness are caused by the role of eosinophils, basophils, neutrophils, and otherinflammatory mediators. The development of medicinal plants in other countries is overgrowing due to manyadverse drug reactions. Chromolaena odorata (L) has been used as a traditional medicine because it hasethnopharmacology effects such as alkaloids, essential oils, phenolics, flavonoids, steroids, phenolic compounds,glycosides, phytates, saponins and tannins which are suppress allergenic. To determine the effect of ethanol extractointment of kirinyuh leaves (Chromolaena odorata (L)) on the levels of eosinophils, basophils, and neutrophils ofallergic that induced in a rabbit nasal mucosa. Experimental research with a pretest-posttest control group designuses rabbits as a research subject. The extract of ethanol ointment from Chromolaena odorata (L) leaf can reduce thenasal mucosa's allergen response. One-way ANOVA statistical analysis showed no significant difference in thenumber of inflammatory cells between basophils, eosinophils, and neutrophils (p0.05;1.00). Furthermore, based onthe analysis of the Kruskal Wallis Test, it showed that there were differences in the number of inflammatory cellsbased on the concentration of the test material, related to the allergen response (p0.05; 0.024) with a strongrelationship (r=0.907). Extracting ethanol ointment from Chromolaena odorata (L) leaf, which is applied topically,can reduce allergic reactions and inflammation.KEYWORDS: allergic rhinitis, eosinophils, basophils, neutrophils, Chromolaena odorata (L)